Genomic instability and myelodysplasia with monosomy 7 consequent to EVI1 activation after gene therapy for chronic granulomatous disease - Stein, Stefan; Ott, Marion G.; Schultze-Straßer, Stephan; Jauch, Anna; Burwinkel, Barbara; Kinner, Andrea; Schmidt, Manfred; Krämer, Alwin; Schwäble, Joachim; Glimm, Hanno; Köhl, Ulrike; Preiss, Carolin; et al. (Nature medicine, 2010)
Gene-modified autologous hematopoietic stem cells (HSC) can provide ample clinical benefits to subjects suffering from X-linked chronic granulomatous disease (X-CGD), a rare inherited immunodeficiency characterized by recurrent, often life-threatening bacterial and fungal infections. Here we report on the molecular and cellular events observed in two young adults with X-CGD treated by gene therapy in 2004. After the initial resolution of bacterial and fungal infections, both subjects showed silencing of transgene expression due to methylation of the viral promoter, and myelodysplasia with monosomy 7 as a result of insertional activation of ecotropic viral integration site 1 (EVI1). One subject died from overwhelming sepsis 27 months after gene therapy, whereas a second subject underwent an allogeneic HSC transplantation. Our data show that forced overexpression of EVI1 in human cells disrupts normal centrosome duplication, linking EVI1 activation to the development of genomic instability, monosomy 7 and clonal progression toward myelodysplasia.
Gesehen am 08.11.2023